What's New in the Treatment of Systemic Lupus Erythematosus - Liossis, Stamatis Nick; Staveri, Chrysanthi (Frontiers in Medicine, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune multisystem disease with a variable presentation and manifestations ranging from mild to severe or even life-threatening. There is an ongoing and unmet need for novel, disease-specific, effective and safe treatment modalities. The aim of this review is to summarize data on SLE treatment that have emerged over the last 2 years. We will put emphasis on studies evaluating potential treatments on severe lupus manifestations such as lupus nephritis. Despite the existence of several therapeutic agents in SLE, the disease keeps causing significant morbidity. It is encouraging that a variety of therapeutic options are currently under investigation, although there are occasional trial failures.